PIODERMA GANGRENOSO - RELATO DE CASO - Marina Nahas Dafico Bernardes; Marcelo Pimenta; Rúbia Carla Maioni Xavier Jubé (UniEVANGÉLICA, 2016)
Objectives: To relate a case of pyoderma gangrenosum is the objective of this article, whose methodology was a revision on the medical records of a public hospital in Goiania with concomitant literature review in the major search sites in the health field. Case report: NPSC, 37 years old, female, white, relates that for a year and six months ago started one burning pain on the dorsum of the left foot, followed by the appearance of ulcerated lesion in this local. Two weeks after, one similar ulcer began in the left forearm, both without trauma, with prodrome of intense local pain, subcutaneous nodules and acute evolution to central ulceration, with erythematous-purplish defined edges and necrotic and purulent base. Negative tests for autoimmune antibodies and for differential diagnosis with tuberculosis, syphilis and hepatitis B and C. In the histopathological of injury: dermis with mixed inflammatory infiltrate (neutrophils, eosinophils and lymphocytes); consistent findings with the clinical hypothesis of pyoderma gangrenosum. Final conclusions: The pyoderma gangrenosum is a rare chronic autoimmune skin disease, characterized by dermal neutrophilia, not infectious and non-neoplastic character, without primary vasculitis, with possible association or not with systemic diseases like rheumatic, inflammatory or hematologic diseases. Theories suggest a neutrophil dysfunction (defects in chemotaxis or hyperreactivity). It affects primarily young women, with peak incidence between twenty and fifty years and has frequent course of exacerbations and remissions. In 50-70% of patients is associate with a systemic disease of base, which was identified in this patient, who had a previous diagnosis of systemic lupus erythematosus.